2014
DOI: 10.2306/scienceasia1513-1874.2014.40.420
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acid composition and anticancer activity against human cancer cell lines of the commercially available fermentation products of Houttuynia cordata

Abstract: A number of Houttuynia cordata fermentation products are commercially available in Thailand. However, their anticancer activity remains to be investigated. In this study, the phenolic acid composition and anticancer activity of two commercialized H. cordata fermentation products were investigated. Reversed phase HPLC was used to identify and quantify phenolic acids. MTT and Annexin V staining assays were used to investigate antiproliferative and apoptosis induction activities, respectively. Seven phenolic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
4
25
0
3
Order By: Relevance
“…Chemotherapy is an effective way to treat many types of cancers, but the cost of treatment is a major public health concern in developing countries. Anti-cancer drugs used to treat patients often are expensive, and most of them cause negative side effects, especially to normal cells that have a high proliferation rate, affecting most cancer patients [3].…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy is an effective way to treat many types of cancers, but the cost of treatment is a major public health concern in developing countries. Anti-cancer drugs used to treat patients often are expensive, and most of them cause negative side effects, especially to normal cells that have a high proliferation rate, affecting most cancer patients [3].…”
Section: Colon Cancermentioning
confidence: 99%
“…The potential biological effects of various constituents of fruits and vegetables suggested a plausible mechanism for protective effects, such as by reducing oxidative damage of DNA or increasing the activity of enzymes able to detoxify carcinogens [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…MTT and Annexin V. staining assays were used to investigate anti-proliferative and apoptosis induction activities. The results showed that commercially available fermentation products of H. cordatacontain several anticancer phenolic acids that may be beneficial in the treatment of human cancer [34].…”
Section: Senawong Et Al (2014)mentioning
confidence: 99%
“…The fermented H. cordata protects the cells (RAW264.7 and RBL-2H3) from LPS-induced toxicity and suppresses the growth of HepG2 cells (human liver cancer cells) [20]. Senawong et al [34] studied the anticancer activity of commercially available fermented H. cordata products (CFH) of Thailand. About seven phenolic compounds were detected in CFH, and some of the CFH exhibited dose-dependentantiproliferative activity against HCT116, HT29, and HeLa cells.…”
Section: Chaiyasut Et Almentioning
confidence: 99%